Analisis Kelancaran Prosedural Matematis Siswa dalam Menyelesaikan Soal Program Linear - Deni Pratidiana; Nunung Muhayatun (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Mathematics is a subject that plays an important role in aspects of life, therefore mathematics lessons are given to students at every level of education so that they are able to master mathematical skills. One of the most important abilities in learning mathematics is the ability to fluency in procedures. This study aims to analyze students' procedural fluency in solving linear program questions in class XI SMA Bidayatul Hidayah. This research uses a qualitative approach that is descriptive. The research instrument used was in the form of test sheets and interview guidelines. The results showed that students who have high mathematical procedural skills are as many as one student because they meet the three indicators used in this study, while as many as two students only meet the second indicator of students' mathematical procedural fluency skills, besides that the other two students have fluency skills. low mathematical procedural because it does not meet all the indicators used in study.